Evaluation of the Antioxidant and Wound Healing Properties of 80% Methanol Extract and Solvent Fractions of the Leaves of Vernonia auriculifera Hiern. (Asteraceae) - Ashenafi E; Abula T; Abay SM; Arayaselassie M; Sori M (Dove Medical Press, 2023)
Ephrem Ashenafi,1 Teferra Abula,1 Solomon Mequanente Abay,1 Mahlet Arayaselassie,2 Moti Sori2 1Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Pathology, School of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Ephrem Ashenafi, Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia, Email ephremashenafiz@gmail.comBackground: The leaves of Vernonia auriculifera (Asteraceae) have traditionally been used to treat wounds in several regions of Ethiopia. The purpose of this study was to assess the wound healing properties of the leaf extract and solvent fractions of V. auriculifera in mice. The leaf extract and solvent fractions of V. auriculifera have also been evaluated for their anti-oxidant properties because of their impact on the wound healing process.Material and Methods: Air-dried leaves were extracted using 80% methanol. They were also successively fractionated with n-hexane, ethyl acetate, and methanol. The residue was then macerated in water for 72 hr. Simple ointment bases were formulated according to British Pharmacopoeia. Thereafter, two types of ointment formulations, 2.5% w/w and 5% w/w, were formulated. Wound healing and acute dermal toxicity studies were performed on mice. To assess free radical scavenging activity, a 2,2-diphenyl-2-picrylhydrazyl free radical (DPPH) assay was performed.Results: In both models, wounds treated with 2.5% and 5% (w/w) of the ME, the aqueous fraction (AQF), methanol fraction (MEF), and ethyl acetate fraction (EAF) ointments demonstrated significant wound healing activity, as shown by enhanced wound contraction, a shortened epithelialization time, increased hydroxyproline content, and enhanced tissue breaking strength. The extract and solvent fractions displayed free radical scavenging activity with IC50 values of 1.2 mg/mL, 1.46 mg/mL, 1.5 mg/mL, and 2.83 mg/mL for ME, AQF, MEF, and EAF, respectively, as compared to 1.42 mg/mL for ascorbic acid.Conclusion: The result of this study indicates that 80% of methanol extract and solvent fractions are endowed with wound healing activity. Additionally, this study has also revealed that ME, AQF, MEF, and EAF have the capacity to scavenge free radicals. The study indicated that the wound healing effect could be attributed to the anti-inflammatory and antioxidant activities.Keywords: Vernonia auriculifera, wound healing activity, excision model, incision model